Overprotective Parenting Dalam Keluarga Modern: Implikasi Terhadap Sosialisasi Dan Kemandirian Sosial Anak - Hanisa Syava Farhata Indilah; Farah Ruqayah (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
Changes in today's lifestyle have altered how parents fulfill their role in educating children within the family. One increasingly common phenomenon is the habit of parents providing excessive protection to their children, known as overprotective parenting. Although the goal is to ensure the child is safe and happy, the way parents raise their children can affect their social development. This article attempts to examine the influence of overprotective parenting on how children learn to interact with others and develop to become more socially independent, using a method of reading and analyzing relevant reference sources. The data was obtained from various studies discussing parenting styles, parent-child relationships, children's social development, and children's ability to live independently. Research shows that overprotection can prevent children from exploring their surroundings, making their own decisions, facing problems, and making friends with others independently. As a result, children more frequently need their parents' help, lack self-confidence, and find it difficult to adapt to a broader social environment. Parenting that provides emotional support and allows children to learn from their experiences is actually better at helping them grow socially and independently. Therefore, it is important to maintain a balance between protecting the child and giving them space to grow, so they can develop into an independent, responsible individual who is capable of interacting healthily with their environment.